M-ary position and three-valued VMAP modem - Yi JIN; Le-nan WU; Jing YU; Lei DENG (Tongxin xuebao)
In order to improve the spectral efficiency and energy efficiency of asymmetry,random-polar and very minimum amplitude and phase (ARP-VMAP) modulated signal simultaneously,an M-ary position and three-valued VMAP modulation was presented,and the receiver based on BP neural network or support vector machine demodulator was also designed.The contrast and analysis of the power spectrum,the −60 dB bandwidth,the spectral efficiency,and the demodulation performance among modulations as the ARP-VMAP,the three-valued VMAP,the M-ary position ARP-VMAP,and the M-ary position and three-valued VMAP,were carried out.Simulation results show that the new modem not only raise spectral efficiency,but also improve demodulation performance significantly.